RANCANG BANGUN ALAT PEMBERITAHUAN OTOMATIS MENGGUNAKAN SENSOR GERAK PIR (PASSIVE INFRA RED) BERBASIS AUDIO UNTUK MEMBERI HIMBAUAN PROTOKOL KESEHATAN DI KANTOR BADAN PENELITIAN, PENGEMBANGAN DAN INOVASI DAERAH KABUPATEN BULELENG - wildanun mukholladun; Nyoman Santiyadnya; Agus Adiarta (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the application of Automatic Device Design Using Audio-Based PIR (Passive InfraRed) Motion Sensors that can be used to assist the delivery process of tools, to find out an efficient and efficient development tool at the office of the Regional Research, Development and Innovation Agency, Buleleng Regency. This research includes the R&D (Research and Development) research model. The study used a questionnaire or questionnaire as a data collection instrument by content experts, media experts, and staff. From the results of the study obtained: the results of the expert trial obtained a value of 100% with a very decent classification, the results of the media expert trial were obtained by 78.12% with a very decent classification, in the small group trial the five respondents were classified as